Disentangling Attention for Frequency and Phonological Markedness in 9- and 12-Month-Old Infants. Issue 4 (2nd October 2018) - ter Haar, Sita Minke; Levelt, Clara Cecilia
ABSTRACT: Infants are thought to be sensitive to frequency in the input as a cue for phonological development. However, linguistic biases such as phonological markedness have been argued to play a role too. Since frequency and markedness are correlated, the two assertions could be different interpretations of data that confound frequency and markedness. In this study we disentangle the two, by testing infants' preferences for syllables contrasting in frequency, balanced for markedness, and for syllables contrasting in markedness, balanced for frequency. We expected a developmental change from frequency-independent to frequency-dependent sensitivity. In addition, we expected an early preference for unmarked structure and a later preference for marked structures, as previously found in child language productions. We find that 9-month-olds prefer phonologically unmarked homorganic patterns, independent of frequency, whereas 12-month-olds prefer marked heterorganic patterns. In contrast to what we expected, only a weak effect for frequency is found and no developmental change.